Transformations of Asteraceae species composition of segetal flora in the prut-Dniester interfluve - І. Т. Palamar (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Bìologìâ, Ekologìâ, 2008)
The investigation of the species composition of segetal flora of the Prut-Dniester interfluve states, that the family Asteraceae takes leading position in the families spectrum. It is determined that during the process of anthropogenesis the species composition of the family Asteraceae underwent the largest transformations. Expansion of the species diversity results from the invasion of the adventive species of North American origin.